Reprints of Rare Papers on Mollusca: Bryant Walker (1918) Synopsis and Classification (Continued from Sterkiana 36) - Bryant Walker (Hello World!, 1970)
The publications of the Museum of Zoology, University of Michigan, consist of two series- the Occasional Papers and the Miscellaneous Publications. Both series were founded and are being supported by Dr. Bryant Walker, Mr. Bradshaw H. Swales and Dr. W. W. Newcomb, except that the cost of the illustrations and of distribution are borne by the University. (Cont.)